The level of tetanus immunity in the population of villages in Bosnia and Herzegovina - Byčenko, B. (1971)
Determination of the level of tetanus immunity in different age groups of a population is important in relation to the results of mass immunization of the population with vaccines containing tetanus toxoid. In this study, the level of tetanus antitoxin in sera from 1053 inhabitants of 6 villages in Bosnia and Herzegovina was determined by means of the passive haemagglutination test. The results show that children from 1 to 14 years of age regularly immunized with DT and DTP vaccines possessed a high level of immunity against tetanus (geometric mean antitoxin titre ≥0.8 IU/ml) and were protected against tetanus in 80-95% of cases. The adult inhabitants (men and women over 29 years of age) were not sufficiently protected against tetanus, the concentrations of antitoxin in their sera being equal to or greater than 0.01 IU/ml in less than 50% of cases.